2020
DOI: 10.1080/1068316x.2020.1849692
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction with life and crime: testing the link

Abstract: This study tests the hypothesis that higher perceptions of satisfaction with life (SWL) are related to lower engagement in crime and deviance. The results can inform prevention, intervention, and policy efforts based on deterrence, general strain, and restorative justice within the criminal and juvenile justice systems. Using a sample of students at two Pennsylvania universities, data were collected using a paper-based, self-reported survey that included measures for their perceptions of SWL, feelings of strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…We indicated above that the research into demographic association with SWL has demonstrated that demographic factors do not consistently associate with reported global SWL (Diener et al, 2003;Olson et al, 2020). Perhaps with the exception of income, there are no consistent results for an association between demographics and satisfaction in life domains (Huebner et al, 2000;Martikainen, 2009;Paiva et al, 2009).…”
Section: Guidance and Cautions For The Integration Of Happiness And Rjmentioning
confidence: 89%
See 3 more Smart Citations
“…We indicated above that the research into demographic association with SWL has demonstrated that demographic factors do not consistently associate with reported global SWL (Diener et al, 2003;Olson et al, 2020). Perhaps with the exception of income, there are no consistent results for an association between demographics and satisfaction in life domains (Huebner et al, 2000;Martikainen, 2009;Paiva et al, 2009).…”
Section: Guidance and Cautions For The Integration Of Happiness And Rjmentioning
confidence: 89%
“…For simplicity, we retain satisfaction with life or SWL hereafter. Olson et al (2020 p. 3) described SWL asthe extent to which a person feels satisfaction with the conditions of their life. It is determined by reflection on the social, historical, and collective experiences that each person has had in life (Argyle, 1987; Martikainen, 2009; Tang & Chan, 2017).…”
Section: Language and Models Of Happinessmentioning
confidence: 99%
See 2 more Smart Citations
“…Resilience, in turn, has been linked to lower reports of criminal deviance (Buonanno et al, 2009;Burt et al, 2017). Satisfaction with life has also been linked to abstinence, recovery, and remission from substance use (Donohue et al, 2003;Laudet et al, 2009;Maccagnan et al, 2020) and with lower reports of crime engagement (MacDonald et al, 2005;Olson et al, 2020;Valois et al, 2001Valois et al, , 2006. Still, much work remains for the two positives.…”
mentioning
confidence: 99%